COMPARATIVE STUDY ON EFFICACY OF CARBON DIOXIDE LASER VERSUS DERMAROLLER WITH PLATELET-RICH PLASMA ON STRIAE DISTENSAE - Dr. Madhulika Gupta; Dr. Tarang Goyal; Dr. Swati Gupta4; Dr. Sumit Sehgal (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Introduction: Striaedistensae, commonly known as stretch marks, are a widespread dermatological concern impacting various populations. These linear scars, characterized by epidermal thinning and alterations in dermal architecture, often affect individuals’ psychological well-being despite being asymptomatic. Clinically, they present initially as reddish or purplish lesions (striaerubra) that progress to pale, wrinkled streaks (striaealba). The etiology involves the breakdown of elastin fibers in the mid-dermis, influenced by hormonal changes, genetic factors, and immune responses. Current treatments aim to reduce inflammation, stimulate collagen production, and improve skin hydration, yet no single modality has been proven definitively effective. This research investigates the relative effectiveness of fractional CO2 laser therapy compared to microneedling combined with platelet-rich plasma (PRP) for the treatment of striaedistensae. Methods: A prospective interventional study was carried out at Muzaffarnagar Medical College & Hospital, where 60 patients with striaedistensae were enrolled from June 2022 to December 2023.Participants were randomly assigned to either fractional CO2 laser therapy or microneedling with PRP. Each group underwent four treatment sessions spaced one month apart. Treatment efficacy was assessed using clinical photography, the Atwal and Davey scoring system, patient satisfaction surveys, and monitoring for adverse events. Results: Fractional CO2 laser therapy demonstrated superior efficacy compared to microneedling with PRP. The fractional CO2 laser resulted in a 33.9% reduction in the Atwal and Davey score for both striaerubra and alba, while microneedling with PRP achieved an 18.6% reduction. Patient satisfaction was notably higher in the fractional CO2 laser group (59.9%) compared to the microneedling with PRP group (26.6%). Both treatments were generally well-tolerated, though fractional CO2 laser therapy was associated with a slightly higher incidence of post-inflammatory hyperpigmentation and scarring. Conclusion: Fractional CO2 laser therapy proves to be more effective than microneedling combined with PRP in enhancing the appearance of striaedistensae and yields greater patient satisfaction. While there are some risks of adverse effects, fractional CO2 laser therapy is a superior choice for treating stretch marks, delivering better clinical results and higher patient preference.Further studies with larger sample sizes and longer follow-up are warranted to confirm long-term benefits and safety.